Proceedings of the 2003 International ACM SIGGROUP Conference on Supporting Group Work 2003
DOI: 10.1145/958160.958216
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for usable patterns of groupware applications

Abstract: Patterns, which are based on in-depth practical experience, can be instructing for the design of groupware applications as sociotechnical systems. On the basis of a summary of the concept of patterns -as elaborated by the architect Christopher Alexander -its adoptions within computer science are retraced and relationships to the area of groupware are described. General principles for patterns within this domain are formulated and supported by examples from a wide range of experience with knowledge management s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…There are also a number of collaboration patterns which can be studied in order to try to understand the coordination mechanisms encapsulated behind those collaboration models (de Vreede and Briggs 2001;Herrmann et al 2003;Pinelle and Gutwin 2006;Zurita et al 2008). The analysis of these patterns could provide some insight on how to coordinate mobile workers' activities; however such research effort is still pending.…”
Section: Related Workmentioning
confidence: 99%
“…There are also a number of collaboration patterns which can be studied in order to try to understand the coordination mechanisms encapsulated behind those collaboration models (de Vreede and Briggs 2001;Herrmann et al 2003;Pinelle and Gutwin 2006;Zurita et al 2008). The analysis of these patterns could provide some insight on how to coordinate mobile workers' activities; however such research effort is still pending.…”
Section: Related Workmentioning
confidence: 99%
“…POSA2 (Schmidt et al, 2000) or the collection of Guerrero and Fuller (1999) that focuses on technical infrastructures for groupware applications. Other collections have focused on specific groupware domains like knowledge management (Herrmann et al, 2003) or group support systems (Kolfschoten et al, 2004). As Erickson (2000) pointed out, pattern languages can serve as a Lingua Franca for human-computer interaction design.…”
Section: Article In Pressmentioning
confidence: 99%
“…Some research works can be found in the literature about collaboration patterns (Verginadis et al, 2010;Herrmann T., et al 2003;Erickson, 2000), but very limited work has been done about their automatic application during software development.…”
Section: Introductionmentioning
confidence: 99%